Time to Review the Role of Surrogate End Points in Health Policy: State of the Art and the Way Forward - Ciani, Oriana; Buyse, Marc; Drummond, Michael; Rasi, Guido; Saad, Everardo D.; Taylor, Rod S. (Value in health, 2017)
The efficacy of medicines, medical devices, and other health technologies should be proved in trials that assess final patient-relevant outcomes such as survival or morbidity. Market access and coverage decisions are, however, often based on surrogate end points, biomarkers, or intermediate end points, which aim to substitute and predict patient-relevant outcomes that are unavailable because of methodological, financial, or practical constraints. We provide a summary of the present use of surrogate end points in health care policy, discussing the case for and against their adoption and reviewing validation methods. We introduce a three-step framework for policymakers to handle surrogates, which involves establishing the level of evidence, assessing the strength of the association, and quantifying relations between surrogates and final outcomes. Although the use of surrogates can be problematic, they can, when selected and validated appropriately, offer important opportunities for more efficient clinical trials and faster access to new health technologies that benefit patients and health care systems.